Biomarkers in sarcopenia: A multifactorial approach - Curcio, Francesco; Ferro, Gaetana; Basile, Claudia; Liguori, Ilaria; Parrella, Paolo; Pirozzi, Flora; Della-Morte, David; Gargiulo, Gaetano; Testa, Gianluca; Tocchetti, Carlo Gabriele; Bonaduce, Domenico; Abete, Pasquale (Experimental gerontology, 2016)
The slow and continuous loss of muscle mass that progresses with aging is defined as “sarcopenia”. Sarcopenia represents an important public health problem, being closely linked to a condition of frailty and, therefore, of disability. According to the European Working Group on Sarcopenia in Older People, the diagnosis of sarcopenia requires the presence of low muscle mass, along with either low grip strength or low physical performance. However, age-related changes in skeletal muscle can be largely attributed to the complex interactions among factors including alterations of the neuromuscular junction, endocrine system, growth factors, and muscle proteins turnover, behavior-related and disease-related factors. Accordingly, the identification of a single biomarker of sarcopenia is unreliable, due to its “multifactorial” pathogenesis with the involvement of a multitude of pathways. Thus, in order to characterize pathophysiological mechanisms and to make a correct assessment of elderly patient with sarcopenia, a panel of biomarkers of all pathways involved should be assessed. •Sarcopenia is defined as a progressive loss of muscle mass and strength with aging.•Sarcopenia is a syndrome characterized by several pathophysiological mechanisms.•Sarcopenia cannot be assessed by the use of a single biomarker.•Biomarkers for each pathophysiological mechanism should be assessed.